Parents' Smoking Behavior and the Incidence of Childhood Pneumonia - Sari, Dwi Poerwita; Firdaus, Achmad Dafir; Fatmawati, Diana Noor (Sarana Ilmu Indonesia (salnesia), 2025)
Factors associated with the incidence of pneumonia include age, sex, low birth weight, immunization status, breastfeeding practices, vitamin A supplementation, nutritional status, residential density, housing characteristics, ventilation, floor type, lighting, humidity, type of cooking fuel, family income, maternal knowledge, as well as maternal factors such as education, age, and exposure to cigarette smoke. This study aimed to determine the relationship between parental smoking behavior and the incidence of pneumonia in children. A quantitative correlational design with a cross-sectional approach was used. The study involved 32 subjects selected through purposive sampling. The results showed that most parents had light smoking behavior (59,3%), and the majority of children did not experience pneumonia (71,9%). A significant relationship was found between parental smoking behavior and the incidence of pneumonia in children, with a Spearman Rank significance value of p = 0,008 (p-value < 0,05). It was important for parents to avoid smoking around children and to create a smoke-free home environment in order to prevent respiratory infections in children.